Conservation Detection Dogs Increase Efficacy for Prey Detection at Carnivore GPS Cluster Sites During Summer. (30th July 2021) - Petroelje, Tyler R.; Fowler, Nicholas L.; Kautz, Todd M.; Lutto, Ashley L.; Davidson, Gregory A.; Beyer, Dean E.; Belant, Jerrold L.
ABSTRACT: Combining carnivore movements with site visits to investigate predation events can inform investigators of carnivore diets, kill rates, and risk factors for prey. However, detecting remains of prey can be challenging when prey is small or when vegetation conceals prey. Conservation detection dogs (CDDs) have assisted with wildlife surveys to locate objects of conservation interest, often improving detection over human counterparts. We hypothesized that CDDs would improve efficacy for detection of prey remains at kill locations compared to human searchers. We compared the efficacy of CDD teams (1 dog, 1 human handler) and technician teams (2 humans) for locating prey remains at 729 carnivore cluster (potential predation) sites in the Upper Peninsula of Michigan, USA, during May to August of 2015. Carnivore species included gray wolves ( Canis lupus ), coyotes ( C. latrans ), bobcats ( Lynx rufus ), and American black bears ( Ursus americanus ). Overall, CDD teams identified prey remains at 2.3 times more clusters, required 42% less search time, and handlers traveled 83% less distance per detected prey remain compared to technician teams. Within carnivore species, CDD teams detected small prey remains at a greater rate than technician teams (4.0–4.3 times greater) for all carnivores except for bobcat which had similar detection rate. Detection of large prey remains (e.g., adult ungulates) was similar between CDD teams and technician teams. Our study supports CDDs ability to outperform humans when searching for objects of conservation interest which are visually cryptic but traceable by scent. Where logistics allow, we recommend use of CDDs over human searchers when it is a priority to locate remains of small prey and when vegetation is dense and may obscure even larger prey items. © 2021 The Wildlife Society. Abstract : Conservation detection dogs improved detection of remains of small prey and search efficiency as compared to humans. Where logistics allow, we recommend use of conservation detection dogs over human searchers when it is a priority to locate remains of small prey and when vegetation is dense and may obscure even larger prey items as these objects are traceable by scent.